The Effectiveness of Educational Games in Mathematics Learning in Elementary Schools: A Systematic Literature Review - Dita Ayu Apriani; Yasinta Mahendra; Berta apriza (MIMBAR PGSD Undiksha, 2025)
Mathematics as one of the basic subjects, has a crucial role in students' cognitive development. However, students often find it difficult to interpret abstract mathematical concepts. The main purpose of this systematic literature review is to examine in depth the effectiveness of using educational games in mathematics learning in elementary schools. The research method used in this article is the Systematic Literature Review (SLR) with the Prisma approach. The results of the study show that during the 2020-2024 period, the integration of educational games in mathematics learning made a positive contribution to students' cognitive development. Educational games not only develop students' academic achievements in the short term, but also help them improve their critical thinking skills, collaboration, and creativity that are useful for life. Based on the results and discussion, it can be concluded that the use of educational games has proven to be effective in mathematics learning in elementary schools. Educational games are able to change the perspective of mathematics learning from being initially difficult to being easier. Therefore, it is recommended for educators to use educational games appropriately in the learning process in the classroom, especially mathematics learning. The implications of this study will provide a comprehensive synthesis of evidence and direct future research on how educational games affect mathematics learning.